Mechanical properties and acoustic emission evolution of water-bearing sandstone under triaxial conditions - Zhang, Lixin; Liu, Guangchao; Wei, Xiujie; Zhang, Yin (Frontiers in Earth Science, 2023)
Abstract：Accidents occur frequently in underground chambers owing to the high-stress environment, poor stability of rocks, and unreasonable mining and construction layout. Significant damage to the deep surrounding rock mass by confined water can result in water inrush and flooding accidents. This study numerically investigated the mechanical properties and acoustic emission (AE) signal evolution mechanism of water-bearing sandstone in deep high-stress mining environments. The results showed that, the lower the confining pressure, the lower is the compressive strength of the specimen, resulting in evident failure. The confining pressure inhibited the radial strain and enhanced the strength of the specimen. Furthermore, under the same confining pressure and different water pressure, the higher the water pressure value, the more evident was the failure phenomenon, and the lower was the peak stress. The water pressure decreased the strength of the specimen and its ability to resist damage.Moreover, for the same water pressure, the smaller the confining pressure, the larger was the maximum AE number and the total cumulative amount of acoustic emissions. When the specimen reached the peak stress and produced macroscopic failure, the AE number reached the maximum value. Finally, the AE activity decreased as the water pressure increased, and the higher the water pressure, the smaller was the cumulative AE number. Owing to the existence of water pressure, the internal structure of the model specimen was affected by the softening effect, which decreased the model strength, thereby suppressing the AE activity of the specimen. Our findings can provide a basis for numerical simulation research on mechanical properties and AE evolution mechanism of waterbearing sandstone under three-way stress state.